IQLIMINING INSON SALOMATLIGIGA TA’SIRI (Surxondaryo viloyati misolida) - Abdimo‘minov, T.A. (SCIENCE and SOCIETY, 2024)
In this article, the impact of the climate of Surkhandarya region on human health was assessed on the basis of analytical conclusions.
Keywords: climate; precipitation; cold days; hot days; Afghan wind; respiratory diseases; dust